Reinterpretasi Hadis Perempuan Di Ruang Publik Perspektif Feminisme Sosialis - Nur Ikhlas; Ahmad Hifni (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Hadith for women is prohibited without a mahram, including one of the topics of hadith that is quite well known, not only for hadith experts, but also warm among jurists. certain, believe that women are prohibited from going without a mahram, other parts of the hadith are temporal so that they are not relevant to use in the current situation and situation. Because the hadith describes the conditions at the time of the Prophet and his companions, not the current conditions. This paper compares the hadith that is forbidden without a mahram with the hadith that can be used by women without a mahram. Then it will try to give a new meaning (reinterpretation) based on the compromise results of the hadiths that seem